Tutela Antecipada na Ação Rescisória - Batista, Marília Volpe Zanini Mendes (2007)
This work had as target the study of the provisional remedy on the rescindable action. A scope more centered in the instituting of the provisional remedy, in the judged thing and the rescindable action was established. The objective was to demonstrate the possibility of the provision of the remedy on the rescindable action, on what, the alteration of article 489 of the Code of Civil Action, leaves no doubt. As such, the concept of jurisdictional remedy and its species was discoursed briefly, also informing on the instrumental character of the civil action. Still, a study was performed on the effectiveness of the process and the provisional remedy, to demonstrate that this is one of the most efficient ways (not to say it is the way) to change the process into an effective and just one. Immediately after, a specific study on the provisional remedy in the civil procedural Brazilian law was made. Also, a study was made on the judged thing and, mainly, on the possibility of it being relative in the cases where it exists serious vice to the sentence or this one is in disagreement with the law, violating the jurisprudence. An exclusive study about the rescindable action was performed. Finally, the central subject of the present work was approached: The possibility of the provision of the remedy on the rescindable action. As such, there was talk about the constitutional guarantees of the due legal process and of the intangibility of the judged thing, a short passage about the constitutional principles and its conflicts was written. Concluding, brief aspects regarding the common points and differences between the precautionary and provisional remedies were presented, with ends of showing that even with the alteration of the article 489 of the Code of Civil Action by the Law # 11.280 of 2006, that foresees the possibility of the rescindable action being suspended by measure of precautionary nature or provision of the remedy, in the essential cases and under the presuppositions predicted under law, the provisional remedy is the best way to plead the suspension of the rescindable jury